CLASS ACTION RESEARCH (CAR) TRAINING FOR TEACHERS IN SDN GAYUNGAN II SURABAYA - Danang Prastyo; Rarasaning Satianingsih; Ida Sulistyawati; Arif Mahya Fanny (Pasundan International of Community Services Journal (PICS-J), 2020)
Professional teachers can be seen from the ability of teachers to produce quality Classroom Action Research (CAR). If seen not all teachers are able to produce research in accordance with CAR standards. Through Community Service Program, Unipa Surabaya PGSD Study Program with the theme of Classroom Action Research Writing (CAR) for Elementary School Teachers in Gayungan II Elementary School in Surabaya is expected to help teachers in producing quality CAR. From the results of the training that has been carried out, it seems that the enthusiasm of the SDN Gayungan 2 Surabaya teacher in following the CAR was very good. The majority of participants felt they needed to get CAR training. Participants feel the benefits after receiving CAR training.